2017
DOI: 10.1016/j.physb.2017.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Surface functionalization of magnetite nanoparticle: A new approach using condensation of alkoxysilanes

Abstract: In this study we report on successful production of two samples (BR15 and BR16) comprising magnetite (Fe 3 O 4) nanoparticles (~10 nm) surface-functionalized via hydrolysis and condensation of alkoxysilane agents, namely 3-aminopropyl-trimethoxisilane (APTS) and N-propyl-trimethoxisilane (NPTS). The as-produced samples were characterized using transmission electron microscopy (TEM), x-ray diffraction (XRD), magnetization measurements (5 K and 300 K hysteresis cycles and zero field-cooled/field-cooled measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Several studies have shown that magnetite nanoparticles exhibit great potential for the development of new materials, mainly due to their magnetic properties and the possibility of functionalizing their surface with different agents such as enzymes [ 8 ], biopolymers [ 9 ], organic particles [ 10 ], chelating moieties [ 11 ], and alkoxysilanes [ 12 ]. Similarly, silica nanoparticles have drawn significant attention due to their stability, low toxicity, and ability to be functionalized with a range of molecules and polymers, which can form improved biomaterials from various hybrid nanomaterials [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that magnetite nanoparticles exhibit great potential for the development of new materials, mainly due to their magnetic properties and the possibility of functionalizing their surface with different agents such as enzymes [ 8 ], biopolymers [ 9 ], organic particles [ 10 ], chelating moieties [ 11 ], and alkoxysilanes [ 12 ]. Similarly, silica nanoparticles have drawn significant attention due to their stability, low toxicity, and ability to be functionalized with a range of molecules and polymers, which can form improved biomaterials from various hybrid nanomaterials [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, nanomaterials with core–shell and york–shell structures have high interfacial polarization due to the synergistic effects of both the cores and shells [ 8 , 22 , 23 , 24 , 25 ]. Therefore, a number of studies have explored nanomaterials with core–shell and york–shell structures to achieve high EM wave absorbing performances [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%